PELAYANAN KESEHATAN TERNAK DI WILAYAH DESA PENGOTAN, KECAMATAN BANGLI, KABUPATEN BANGLI - Suarsana, I.N.; Kardena, I.M.; Arjentinia, I.P.G.Y. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana Mengabdi, 2018)
Disease is an important factor in the production system and livestock productivity. Efforts to control the disease can be done through the prevention of disease and or treatment of sick livestock. Health services of cattle and pigs are carried out in Pengotan Village, Bangli District, Bangli Regency in the grant program of KKN PPM. The purpose of this activity is to maintain and improve the health of bali cattle and pigs so that the productivity and production of livestock can be improved. Approach method used is by involving members of Gapoktan Asta murti or individually who have livestock. Clinically cattle observed exterior conditions and interviews with owners to find out the initial conditions of livestock health and subsequent medicine action. The results of livestock health service activities show only 2 types of livestock are given health services namely bali cattle and pigs. Overall health services to bali cattle as many as 303 heads and 146 pigs. The service was carried out in 8 dusun in Pengotan village with details of dusun Besange 108, dusun Sunting 41, Dusun Penyebeh 39, Dusun Yoh 29, Dusun delod village 72 heads, Dusun dajan umah 43, and Dusun Tiying 117. Type of health services provided is the provision of vitamins, worm medicine and sparying of ectoparasit. It was concluded that cattle and pigs in Pengotan village are in good condition. Intervention with the provision of vitamins, worm medicines and ectoparasit drugs improves the performance of bali cattle and pigs